Asian guidelines for urinary tract infection in children. Issue 11 (November 2021) - Yang, Stephen S.; Tsai, Jeng-Daw; Kanematsu, Akihiro; Han, Chang-Hee
Abstract: The followings are the level of evidence (LE) and grade of recommendation (GR) on pediatric UTI in Asia. Classification according to the sites of infection (lower versus upper tract), the number of episode (first versus recurrent), the severity (simple versus severe), or the existence of complicating factor (uncomplicated versus complicated) is useful to differentiate children with UTI whether they are at risk of renal damage or not (LE: 2, GR: B). Diagnosis of UTI requires both urinalysis that suggests infection and positive urine culture (LE:3, GR B). For pre-toilet trained children, urine specimen for culture should be collected by urethral catheterization or suprapubic aspiration. For toilet trained children, midstream clean catch urine is reliable (LE: 3, GR: A). Urine culture is considered positive if it demonstrates growth of a single bacterium with the following colony counts: (1) any growth by suprapubic aspiration, (2) >5 × 104 CFU/ml by urethral catheterization, or (3) >100, 000 CFU/ml by midstream clean catch (LE:3, GR: B). For children with febrile UTI, renal and bladder ultrasonography (RBUS) should be routinely performed as soon as possible (LE: 3, GR: C). RBUS should be followed up 6 months later in children with acute pyelonephritis and/or VUR (LE: 3, GR: C). Acute DMSA scan can be performed when severe acute pyelonephritis or congenital hypodysplasia is noted on RBUS or when the diagnosis of UTI is in doubt by the clinical presentation (LE: 3, GR: C). Late DMSA scan (>6 months after the febrile UTI) can be performed in children with severe acute pyelonephritis, high-grade VUR, recurrent febrile UTIs, or abnormal renal parenchyma on the follow-up RBUS (LE: 3, GR: C). Top-down or bottom-up approach for febrile UTI is suggested for the diagnosis of VUR. For top-down approach, VCUG should not be performed routinely for children after the first febrile UTI. VCUG is indicated when abnormalities are apparent on either RBUS or DMSA scan or both (LE: 2, GR: B). VCUG is also suggested after a repeat febrile UTI (LE:2, GR: B). Appropriate antibiotic should be given immediately after urine specimen for culture has been obtained (LE:2, GR: A). Initiating therapy with oral or parenteral antibiotics is equally efficacious for children (>3 months) with uncomplicated UTI (LE: 2: GR: A). The choice of empirical antibiotic agents is guided by the expected pathogen and the local resistance patterns (LE: 2, GR: A). For children with febrile UTI, the total course of antibiotic therapy should be 7–14 days (LE: 2, GR: B). Circumcision may, but not definitively, reduce the risk of febrile UTI in males and breakthrough febrile UTI in males with VUR. Circumcision should be offered to uncircumcised boys with febrile UTI and VUR in countries where circumcision is accepted by the general population (LE: 3, GR: B), while in countries where childhood circumcision is rarely performed, other measures for febrile UTI/VUR should be the preferred choice (LE: 4, GR: C). Bladder bowel dysfunction (BBD) is one of the key factors of progression of renal scarring (LE: 2). Early recognition and management of BBD are important in prevention of UTI recurrence (LE:2, GR: A). Antibiotic prophylaxis to prevent recurrent febrile UTI is indicated in children with moderate to high grade (III–V) VUR (LE: 1b, GR: A). Surgical intervention may be used to treat VUR in the setting of recurrent febrile UTI because it has been shown to decrease the incidence of recurrent pyelonephritis (LE: 2, GR: B).